2020
DOI: 10.1111/1348-0421.12764
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on the relationship between toxin production and psm‐mec mutations in MRSA isolates in Thailand

Abstract: In this present study, we investigated the phenol‐soluble modulin (psm‐mec) mutations, the staphylococcal cassette chromosome mec (SCCmec) types, and toxin production in 102 methicillin‐resistant Staphylococcus aureus (MRSA) isolates from the northeast and central regions of Thailand. The MRSA isolates carrying ‐7T>C psm‐mec in Type II SCCmec (n = 18) and the MRSA isolates carrying no psm‐mec in Type IV (n = 8) or Type IX SCCmec (n = 4) had higher hemolytic activity against sheep erythrocytes than MRSA isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Indeed, we found that the psm-mec gene and the psm-mec srRNA were exclusive to this ST/Agr group (Figure 1, Table 1) and had 100% sequence identity to those described in S. aureus and S. epidermidis [49]. A characterized -7 T > C mutation in the psm-mec promoter region, which attenuates PSM-mec expression, is present in a subset of hospital-associated methicillin-resistant S. aureus (HA-MRSA) strains harboring SCCmec Type II [41,[50][51][52]. However, the psm-mec promoter region in our ST71/Agr group III isolates did not harbor this mutation, indicating host-species-independent specificity for SCCmec Type II elements.…”
Section: St71/agr Group IIImentioning
confidence: 94%
“…Indeed, we found that the psm-mec gene and the psm-mec srRNA were exclusive to this ST/Agr group (Figure 1, Table 1) and had 100% sequence identity to those described in S. aureus and S. epidermidis [49]. A characterized -7 T > C mutation in the psm-mec promoter region, which attenuates PSM-mec expression, is present in a subset of hospital-associated methicillin-resistant S. aureus (HA-MRSA) strains harboring SCCmec Type II [41,[50][51][52]. However, the psm-mec promoter region in our ST71/Agr group III isolates did not harbor this mutation, indicating host-species-independent specificity for SCCmec Type II elements.…”
Section: St71/agr Group IIImentioning
confidence: 94%